KVANT TASVIRLARNI GIBRID ALGORITMLAR YORDAMIDA IShLASh - Muhamediyeva, D.T.; Ametova, G.E. (SCIENCE and SOCIETY, 2025)
Image processing is a one-dimensional signal processing that uses Gabor transforms and Gaussian translations and modulations. It includes steps such as image reading, editing, enhancement, segmentation, object detection, and feature analysis. Hybrid quantum algorithms for working with large amounts of data may be an effective tool for analyzing images processed in real time in the near future.